A highly active perovskite anode with an in situ exsolved nanoalloy catalyst for direct carbon solid oxide fuel cells. Issue 32 (4th August 2021) - Ma, Minjian; Yang, Xiaoxia; Ren, Rongzheng; Xu, Chunming; Qiao, Jinshuo; Sun, Wang; Sun, Kening; Wang, Zhenhua
Abstract : A novel layered perovskite, with an in situ exsolved FeNi3 catalyst for the reverse Boudouard reaction, is developed as the anode of direct carbon solid oxide fuel cells. The highly active alloy–perovskite interface greatly promotes anode reactions. Abstract : Effective utilization of carbonaceous fuels is essential to address the economic and environmental challenges in the future. Direct carbon solid oxide fuel cells (DCSOFCs) offer a promising solution, but their performance is hindered by the sluggish anode processes and poor stability. Herein, a novel layered perovskite, (PrBa)0.95 Fe1.6 Ni0.2 Nb0.2 O5+ δ (PBFNN), is developed as a highly effective anode material for DCSOFCs. FeNi3 nanoparticles on the perovskite substrate are in situ exsolved under the reduction of carbon, and the resulting alloy–perovskite interfaces can promote efficient reverse Boudouard reaction (RBR) by the optimized CO2 capture and RBR activation. Therefore, the carbon fuel can be efficiently converted into CO because of the highly active RBR on the surface of the PBFNN anode, which further promotes the electrochemical oxidation of CO, leading to enhanced electrochemical performance of the anode. An electrolyte-supported DCSOFC employing the PBFNN anode yields superior performances but using additive-free carbon fuels, and delivers a peak power density of 605.1 mW cm −2 at 800 °C and superior stability over 120 h at 750 °C. Our work highlights that PBFNN is a high-performance and robust alternative perovskite anode for DCSOFCs.